Care and anger motives in social dilemmas - Patrick Ring; Christoph A. Schütt; Dennis J. Snower (Theory and Decision, 2023)
This paper provides evidence for the following novel insights: (1) People's economic decisions depend on their psychological motives, which are shaped predictably by the social context. (2) In particular, the social context influences people's other-regarding preferences, their beliefs and their perceptions. (3) The influence of the social context on psychological motives can be measured experimentally by priming two antagonistic motives—care and anger—in one player towards another by means of an observance or a violation of a fairness norm. Using a mediation approach, we find that the care motive leads to higher levels of cooperation which are driven by more optimistic beliefs, a different perception of the game as well as by a shift towards more pro-social preferences.
Keywords: 300; Social dilemma; Motivation; Pro-social preferences; Stability of preferences; Priming; Norm violation